2010
DOI: 10.1051/0004-6361/201014196
|View full text |Cite
|
Sign up to set email alerts
|

Brightness map of the zodiacal emission from the AKARI IRC All-Sky Survey

Abstract: The first Japanese infrared space mission AKARI successfully scanned the whole sky with its two main instruments, the Infrared Camera (IRC) and the Far-Infrared Surveyor (FIS). The AKARI All-Sky Survey provides us with an invaluable opportunity to examine the zodiacal emission (ZE) over the entire sky in the leading as well as the trailing direction of the Earth's motion. We describe our efforts to reduce the ZE brightness map from the AKARI's survey in the 9 μm waveband. Compared with the interplanetary dust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…However, from the results of the IRAS observations, it was found that there are many small-scale structures in the ZL distribution, http://pkas.kas.org such as asteroidal dust bands and a circumsolar resonance ring (Low et al, 1984;Dermott et al, 1984). It was also found that the sky brightness near the ecliptic plane observed with the IRAS and COBE/DIRBE is brighter towards the direction that trails the Earth's motion than towards the leading direction (Dermott et al, 1994;Reach et al, 1995), and this is confirmed with the AKARI mid-IR observations (Pyo et al, 2010).…”
Section: Introductionsupporting
confidence: 56%
“…However, from the results of the IRAS observations, it was found that there are many small-scale structures in the ZL distribution, http://pkas.kas.org such as asteroidal dust bands and a circumsolar resonance ring (Low et al, 1984;Dermott et al, 1984). It was also found that the sky brightness near the ecliptic plane observed with the IRAS and COBE/DIRBE is brighter towards the direction that trails the Earth's motion than towards the leading direction (Dermott et al, 1994;Reach et al, 1995), and this is confirmed with the AKARI mid-IR observations (Pyo et al, 2010).…”
Section: Introductionsupporting
confidence: 56%
“…The Japanese satellite AKARI, a satellite dedicated to IR astronomical observations, was the third mission to survey the whole sky at mid-and far-IR wavelengths (Murakami et al 2007). Although most of the smooth ZE structure seen in the AKARI mid-and far-IR images can be reproduced well with the Kelsall or the Wright/Gorjian models, there are discrepancies on small scales (Pyo et al 2010;Kondo et al 2016). In particular, the intensities and the ecliptic latitudes of the peak positions of the asteroidal dust bands and the MMRs cannot be precisely reproduced with these models (Pyo et al 2010;Doi et al 2015;Kondo et al 2016).…”
Section: ±2mentioning
confidence: 97%
“…To determine the brightness distribution of the ZE and the spatial structure of the IPD, fullsky surveys obtained with IR satellites are particularly powerful (e.g., Hauser et al 1984;Reach 1992;Reach et al 1997;Fixsen & Dwek 2002;Pyo et al 2010;Planck Collaboration et al 2014). …”
Section: ±2mentioning
confidence: 99%
“…Kelsall et al (1998) made an IPD cloud model based on the COBE 10 photometric band data (hereafter the Kelsall model). This model has been used for removal of the zodiacal light from IR maps such as the IRAS, COBE, and http://pkas.kas.org AKARI maps (Miville-Deschênes & Lagache, 2005;Kelsall et al, 1998;Pyo et al, 2010). However, the Kelsall model does not fully reproduce the distribution of the IPD cloud; for example, there remains a residual component of the zodiacal light (∼1 MJy sr −1 ) around the ecliptic plane in the COBE 12 and 25 µm maps ( Figure 2c in Kelsall et al 1998).…”
Section: Introductionmentioning
confidence: 99%